Pathology and molecular characterization of classical swine fever virus from piggery units in Haryana - MOUDGIL, P; PRAKASH, A; JINDAL, N; LATHER, D; GUPTA, R (The Indian Journal of Animal Sciences, 2021)
Classical swine fever (CSF) is a highly contagious viral disease of pigs and is responsible for significant economic losses due to high morbidity and mortality. Pigs from nine different piggery units in Haryana were investigated for CSF suspected outbreaks during July 2017-June 2019. On the basis of clinical signs, pathology, reverse transcriptase polymerase chain reaction (RT-PCR) and sequencing, the disease in all piggery units was confirmed as CSF. The overall morbidity rate, cumulative mortality and case fatality rate (CFR) due to CSF in these units were 14.3, 9.3% and 65.5%, respectively. Age-wise statistical analysis identified no significant difference in morbidities and mortalities among three age groups, i.e. adult, young and piglets. However, there was a significant difference in CFR with highest among piglets (79.3%) followed by young (68.9%) and adults (45.1%). Seasonal analysis revealed highest cumulative mortality and CFR in winter (29.9% and 91.1%, respectively) followed by rainy season (24.3% and 69.9%, respectively). The findings of the present study are of significant veterinary importance to check the dissemination of CSFV by prompt diagnosis which would help in imposing control measures for minimizing the losses suffered by the piggery units of Haryana, India.